Implementation Of Pursed Lip Breathing And Semi Fowler Position in COPD Patients Which Get Nebulizer in IGD: A Literature Review - Ariefkhoerulummah Nurgiyanta; Galih Noor Alivian (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Background: Chronic obstruction of pulmonary disease (COPD) is a pulmonary disease caused by the blockage of the air flow channel that occurs much in Indonesia due to the high exposure to the risk factors causing COPD such as the habit of smoking and unhealthy environment. The obstruction of the respiratory tract that occurs in COPD patients is usually characterized by shortness of breath. Various ways can be done to overcome shortness of breath is with pharmacological therapy in the form of nebulizer therapy. One of the effective non-pharmacological therapies to reduce shortness of breath with pursed lip breathing therapy and the giving of semi Fowler position. Objectives: Identify the research articles that display the results of analysis of the introduction of pursed lip breathing and the provision of semi Fowler in COPD patients who get therapy nebulizer in IGD space Research Method: The search for articles is done electronically using a Sience Direct, NCBI and Google Scholar databases. The search for the article used is the last 5 years. Keyword in search